Object-oriented modelling and design (Prentice Hall, 1991)
This volume presents a new object-oriented software development methodology - from analysis, through design, to implementation. Key features of the book include a focus on high-level, front-end conceptual processes of analysis and design, rather than just on the low-level, back-end implementation steps of programming; coverage of the entire development life cycle - analysis, design, implementation without a change of notation at each stage; a presentation of graphical notation and methodology independent of any particular programming language; case studies of industrial object-oriented applications developed by the authors; and examples and exercises that bring out fine points, summary lists of concepts and methodology steps, and almost 300 diagrams.